The Influence of Work Environment on Employee Performance with Digital Literacy as a Moderating Variable - Deewar Mahesa; Apriani Riyanti; Fransiska Ekobelawati; Muhamad Risal Tawil; Ridwan, Ridwan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study investigates the relationship between Work Environment and Employee Performance, and examines the role of Digital Literacy as a moderating variable in this relationship. Employee performance is a vital indicator of organizational success. The quality of the work environment is believed to be a major predictor of performance, but the effectiveness of the work environment in the digital era is highly dependent on employees' ability to utilize technology. This study specifically aims to determine whether Digital Literacy strengthens or weakens the influence of the work environment on performance. The research method used is quantitative with a survey design. The population of this study is permanent employees in the creative industry sector in Bandung City, with a sample of 150 respondents selected through a purposive sampling technique. Data were collected using a validated and tested questionnaire for reliability, measuring variables of Work Environment (physical and non-physical), Employee Performance, and Digital Literacy. Data analysis was performed using EViews 12 software, through the stages of Multiple Linear Regression analysis and Moderated Regression Analysis (MRA) by estimating the interaction model. Classical assumption tests, including heteroscedasticity and multicollinearity tests, were also conducted using EViews to ensure the validity of the regression model. The results showed that the Work Environment has a positive and significant influence on Employee Performance. Crucial findings from the MRA analysis using EViews prove that Digital Literacy significantly moderates the relationship (significant interaction variable coefficient). The moderation that occurs is strengthening (strengthening effect), which indicates that the higher the level of digital literacy possessed by employees, the greater the contribution of a positive work environment to improving their performance. The managerial implication of this study is the need for synergy between work facility improvement policies (Work Environment) and technology utilization competency improvement programs (Digital Literacy) to achieve optimal Employee Performance. Keywords: Work Environment, Employee Performance, Digital Literacy, Moderated Regression (MRA), EViews.